Peran Keluarga dalam Meningkatkan Kesejahteraan Lansia - Fauziah Nasution; Fadilah Rahmi Nasution; Nazala Putri Hutasuhut; Rohima Dinda Kusumai; Zahra Aulia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
As life expectancy and the number of elderly people increase in many countries, the welfare of the elderly is becoming an increasingly important issue. In this context, the family plays an important role in improving the physical, mental and social quality of life of the elderly. This research aims to determine the role of the family in improving the welfare of the elderly. This research method uses a qualitative approach and involves literature study, data collection techniques using interview methods and literature research. This research discusses that the family provides important support for the elderly in terms of physical care, emotional support, economic resources and social involvement. However, from the research results, the author found that the elderly people interviewed felt that family members had limited time in terms of dividing their time between work and visiting and exchanging stories.